2002
DOI: 10.1084/jem.20011194
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Complex of the Human α/β T Cell Receptor (TCR) HA1.7, Influenza Hemagglutinin Peptide, and Major Histocompatibility Complex Class II Molecule, HLA-DR4 (DRA0101 and DRB10401)

Abstract: The α/β T cell receptor (TCR) HA1.7 specific for the hemagglutinin (HA) antigen peptide from influenza A virus is HLA-DR1 restricted but cross-reactive for the HA peptide presented by the allo-major histocompatibility complex (MHC) class II molecule HLA-DR4. We report here the structure of the HA1.7/DR4/HA complex, determined by X-ray crystallography at a resolution of 2.4 Å. The overall structure of this complex is very similar to the previously reported structure of the HA1.7/DR1/HA complex. Amino acid seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
203
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(219 citation statements)
references
References 77 publications
15
203
1
Order By: Relevance
“…The binding assay demonstrated that this peptide was good at binding to DR1 and DR2a, but not to DR4, DR10, and DR2b. The core for DR2a was IVIALAGNK, which lacks Leu 4 and Lys 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The binding assay demonstrated that this peptide was good at binding to DR1 and DR2a, but not to DR4, DR10, and DR2b. The core for DR2a was IVIALAGNK, which lacks Leu 4 and Lys 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the structural features of allogeneic TCR-pMHC complexes (8)(9)(10)(11)). An overall assessment of these structures is that rather than demonstrating features that are clearly characteristic of alloreactivity, they illustrate features similar to traditional syngeneic complexes of TCRs with peptides presented by self-MHC (3,12,13).…”
mentioning
confidence: 99%
“…Recombinant α-gliadin/DQ8 protein containing the deamidated peptide sequence QQYPSGEGSFQPSQENPQ was expressed in S2 Drosophila cells and purified as previously described (55). TATD (1,3,6,8-tetraaza-tricyclo[4.4.1.13,8]dodecane) Seattle, Washington, USA) or from published literature (clones 13, 22, and 38, which are DQ8 restricted; clone 233, which is DQ2 restricted; and C7CH17, which is DR4 restricted) (31,32,34,56). Supplemental Table 9 lists each TCR transductant, its corresponding peptide, and its MHC class II restriction.…”
Section: Methodsmentioning
confidence: 99%